Good dairy farming practices (GDFP) implementation on smallholder dairy farmers in East Java, Indonesia - Tri Eko Susilorini; Puguh Surjowardojo; Rini Dwi Wahyuni; Suyadi Suyadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
GDFP is a standard guideline for producing good milk quality and efficient production system. GDFP implementation has been less attention among the dairy smallholder farmers. The smallholder farmers are classified into three categories depending on animal ownership; strata 1 (1-3 AU), strata 2 (4-6 AU), and strata 3 (>7 AU). This research determines the score of GDFP implementation on smallholder farmers in East Java. The total respondents were 56, with 325 dairy cattle. A questionnaire and field observations were used to collect data using the survey method. The farmers were interviewed using a prepared questionnaire with general information about their farms and questions about GDFP implementation. The result showed that the score of GDFP implementation in all strata of smallholder farmers in East Java Indonesia in 6 aspects as follows: animal health was  “good enough” (score  2.68-2.70), milking hygiene was “good” (score 3.19-3.42), nutrition was “good enough” (score 2.86-2.97) in strata I and III and “good” for strata II (score 3.03), animal welfare was “good enough” (2.56-2.60), the environment was "good enough" (2.34-2.50) and socio-economic management is “not good” (score GDFP = 1.60-1.92).